German epic theater and the floating theater in Iraq / Abdul Jabbar Hassan’s experience as an example - Assistant Professor: Bahaa Mahmood Alwan (Journal of College of Education, 2024)
In this research titled (Common points between epic theater and Abdul-Jabbar Hassan’s experience in the marshes of Iraq), it is a comparative study of the experience of the floating theater in the marshes of Iraq and a comparison of this experience with the German epic theater founded by the great German writer Bertolt Brecht. During the research we find many common points between the two theaters mentioned. As part of the research, the focus is on two scenes from one of the plays that Abdul-Jabbar Hassan performed in the marshes of Iraq. Likewise, in the conclusions, we find a close connection between the two theatres. The experience of artist Abdul-Jabbar Hassan is considered one of the pioneering experiences in theater in Iraq and the world. The research also includes an overview of epic theater, as well as the writers Abdul-Jabbar Hassan and Bertolt Brecht.